2020
DOI: 10.48550/arxiv.2003.07816
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Capacitive storage in mycelium substrate

Abstract: The emerging field of living technologies aims to create new functional hybrid materials in which living systems interface with artificial ones. Combining research into living technologies with emerging developments in computing architecture has enabled the generation of organic electronics from plants and slime mould. Here, we expand on this work by studying capacitive properties of a substrate colonised by mycelium of grey oyster fungi, Pleurotus ostreatus. Capacitors play a fundamental role in traditional a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

7
1

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 48 publications
(50 reference statements)
0
8
0
Order By: Relevance
“…In [20] we proposed to develop a structural substrate by using live fungal mycelium, functionalise the substrate with nanoparticles and polymers to make mycelium-based electronics [21,22,23], implement sensorial fusion and decision making in the mycelium networks [24] and to grow monolithic buildings from the functionalised fungal substrate [25]. Fungal buildings would self-grow, build, and repair themselves subject to substrate supplied, use natural adaptation to the environment, sense all that humans can sense.…”
Section: Introductionmentioning
confidence: 99%
“…In [20] we proposed to develop a structural substrate by using live fungal mycelium, functionalise the substrate with nanoparticles and polymers to make mycelium-based electronics [21,22,23], implement sensorial fusion and decision making in the mycelium networks [24] and to grow monolithic buildings from the functionalised fungal substrate [25]. Fungal buildings would self-grow, build, and repair themselves subject to substrate supplied, use natural adaptation to the environment, sense all that humans can sense.…”
Section: Introductionmentioning
confidence: 99%
“…This is because living mycelium networks are active, i.e. they generate spikes of electrical potential [5] and spikes of resistance [7], capacitive [12] and memfractive properties [13].…”
Section: Discussionmentioning
confidence: 99%
“…In our previous studies, we reported that the oyster fungi Pleurotus djamor exhibit trains of electrical potential spikes similar to action potential spikes [4,5,6,7]. Our initial assumption was that spike trains might reflect increasing mycelium propagation in the substrate, nutrient and metabolite transport, and communication processes within the mycelium network.…”
Section: Introductionmentioning
confidence: 98%